Perancangan dan Implementasi Sistem Otomatisasi Transfer dan Separasi Bahan Bakar HFO Menggunakan PLC Siemens pada Kapal MV. XYZ - Muhammad Arham; M.Ilham Nur; A.Aswin Salam (Fakultas Teknik UPRI, 2024)
This study aims to design an automated fuel transfer and separation system using Siemens PLC onthe MV. XYZ vessel, integrate it with the existing ship management system, and identify keyparameters that need to be monitored and controlled within the system. The research methodsinclude experimentation and system simulation, observation, interviews, and documentation. Theanalysis is conducted by comparing the conditions before and after the implementation of theautomation system. The results indicate that the automated system enables fuel processing from thestorage tank to the settling tank over 24 hours, followed by transfer to the service tank every 8hours automatically. The system utilizes high and low-level sensors as inputs to control outputssuch as pumps, separators, valves, and heaters. The system interface is designed to separate eachsubsystem—transfer, separation, and circulation—while remaining fully integrated, allowing crewmembers to monitor the entire process efficiently. This system has proven to enhance the efficiencyand reliability of fuel management on board.